Value-added selling : how to sell more profitably, confidently, and professionally by competing on value, not price / Thomas P Reilly; Paul Reilly, (Sales training consultant) - Reilly, Thomas P.
Value-Added Selling, 4th Edition offers proven strategies and tactics to help you not only close more sales but improve repeat business without compromising on price. You’ll learn how to anticipate the needs, wants, and concerns of buyers from the very beginning of the sales process. The book shows how to compete more profitably by selling value, not price.